Analisis Strategi Pemasaran Untuk Meningkatkan Penjualan Laptop Asus Pada Belilaptop.id Cabang Tangerang - Liani, Yufia Jupri; Widyawan, Bisma (JAMBIS : Jurnal Administrasi Bisnis, 2024)
Marketing  strategy  is  crucial  for  business  success.  This  research  aims  to  identify  marketing strategies and obstacles in increasing sales of Asus Laptops at Belilaptop.id Tangerang Branch. This research uses a descriptive qualitative method with data collection including observation, interviews with 5 (five) informants, and documentation. Based on marketing strategies using STP (Segmenting, Targeting, Positioning) and the 4P Marketing Mix (Product, Price, Place, Promotion), the results of this research show that to face intense competition in similar fields, companies are required to continue to innovate such as maintaining quality and improving promotional campaigns. Belilaptop.id use of the marketplace and product demos as promotional media has been quite effective. This research  identified  inhibiting  factors:  many  competitors  selling  similar  products,  other  brands offering lower prices, low human resources, and limited stock availability of Asus laptops. To overcome obstacles by using influencer services, setting similar prices both in stores and in the marketplace, and paying attention to the availability of Asus Laptop stock